2020
DOI: 10.1007/978-3-030-39540-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Working Together with Conversational Agents: The Relationship of Perceived Cooperation with Service Performance Evaluations

Abstract: Conversational agents are gradually being deployed by organizations in service settings to communicate with and solve problems together with consumers. The current study investigates how consumers' perceptions of cooperation with conversational agents in a service context are associated with their perceptions about agents' anthropomorphism, social presence, the quality of the information provided by an agent, and the agent service performance. An online experiment was conducted in which participants performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…The agents' treatments elicited statistically significant large differences in people's perceptions of the agents sense of agency, ( ) F 2, 120 = 77. 33 . Post hoc analyses using Bonferroni correction revealed that people perceived a human to have higher agency and experience than a humanoid social robot and a disembodied agent (see Figures 5 and 6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The agents' treatments elicited statistically significant large differences in people's perceptions of the agents sense of agency, ( ) F 2, 120 = 77. 33 . Post hoc analyses using Bonferroni correction revealed that people perceived a human to have higher agency and experience than a humanoid social robot and a disembodied agent (see Figures 5 and 6).…”
Section: Methodsmentioning
confidence: 99%
“…what it looks like, its physical presence, how it moves, etc.). In addition, other cues of embodiment are driven by a human interaction partner's cognitive reconstruction [30], wherein their beliefs or expectations about an agent further shape perception and behaviour [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…communicate in a human-like way are often evaluated, perceived and described as such [1] [14]. Accordingly, these are often reported as promoting users' engagement in online settings [5] [17].…”
mentioning
confidence: 99%
“…A previous study entails that when chatbot's actions were perceived to comply with positive moral intentions, i.e., being more cooperative, it was perceived as more anthropomorphic and to be providing a better quality of information. Accordingly, it was evaluated more positively in terms of service performance (Laban & Araujo, 2020). Moreover, anthropomorphic cues were found to positively affect consumers' purchase intentions, attitudes, and brand liking when used for branding products (Delbaere et al, 2011;Hart & Royne, 2017;Laksmidewi et al, 2017).…”
Section: Anthropomorphic Cuesmentioning
confidence: 99%
“…The extent to which an agent can exhibit and imitate human characteristics is simulated by its anthropomorphic cues; these are visual or behavioral cues that resemble human characteristics and trigger anthropomorphic perceptions of the agent (de Visser et al, 2016). Communicating recommendations through a dialogue and natural language, while sustaining a human-like identity (i.e., having a human name and talking in first-person singular pronouns), constitutes potential anthropomorphic cues that can prime an individual's perception of recommender agents (Araujo, 2018;Daniel et al, 2018;Laban & Araujo, 2020). Furthermore, users' perceptions of agents are driven by their cognitive reconstruction, wherein their beliefs or expectations about an agent further shape perception and behavior (Cross, Ramsey, Liepelt, Prinz, Hamilton, 2016).…”
Section: Anthropomorphic Cuesmentioning
confidence: 99%